PENGARUH PENGGUNAAN MEDIA GAMBAR TERHADAP KETERAMPILAN PROSES SAINS OLEH SISWA - Nur Apriani; Tri Jalmo; Berti Yolida (Universitas Lampung, 2013)
The purpose of research were to know the influence of picture media towards increase of student’s science process skill. The research was a quasi-experimental research by pretest posttest group equivalent design. The samples of research were students from VIIIA and VIII B which chosen from population by purposive sampling method. Data of this research were quantitative and qualitative data. Quantitative data obtained from the average value of pretest, posttest and N-gain which statistically analyzed with t-test and U-test. The Result of research showed that the application of picture media affect student’s SPS significantly. The increase of student’s SPS is showed by average value of N-gain (68.00). All indicator of student’s SPS increased with average value of N-gain (67.35). The average percentage of student’s learning activities is in good criteria (80.20%) Besides, most of students gave positive response in application of picture media. Penelitian ini bertujuan untuk mengetahui pengaruh media gambar terhadap peningkatan KPS oleh siswa. Penelitian ini adalah penelitian kuasi eksperimental dengan desain pretes-postes kelompok ekuivalen. Sampel penelitian ini adalah kelas VII2 dan VII3 yang dipilih dari populasi secara purposive sampling. Data penelitian ini berupa data kuantitatif dan kualitatif. Data kuantitatif diperoleh dari rata-rata nilai pretest, posttest dan N-gain pada materi Klasifikasi Makhluk Hidup yang dianalisis dengan uji t dan uji U. Hasil penelitian menunjukkan bahwa penggunaan media gambar berpengaruh sigifikan terhadap peningkatan KPS oleh siswa. Peningkatan KPS siswa ditunjukkan dengan nilai rata-rata N-gain (68,00). Semua indikator KPS siswa mengalami peningkatan dengan nilai rata-rata N-gain (67,35). Rata-rata persentase aktivitas belajar siswa berkriteria baik yaitu 80,20% Selain itu, sebagian besar siswa memberikan tanggapan positif terhadap penggunaan media gambar. Kata kunci: KPS, Klasifikasi Makhluk Hidup, Media Gambar.